Xamarin Studio for Android programming : a C# cookbook : over 50 hands-on recipes to help you get to drips with Xamarin Studio and C# programming to develop market-ready Android applications /: a C# cookbook : over 50 hands-on recipes to help you get to drips with Xamarin Studio and C# programming to develop market-ready Android applications. (2015) - Nayrolles, Mathieu
No abstract available